AB0487 Decreased SLE Disease Activity and Corticosteroid Usage and NO Renal Flares during Belimumab Treatment. (10th June 2014) - Parodis, I.; Svenungsson, E.; Axelsson, M.; Gunnarsson, I.
Abstract : Background: Belimumab is a recombinant monoclonal antibody that specifically binds to soluble B-lymphocyte stimulator, thereby reducing autoantibody levels. It is the only biologic agent approved for treatment of Systemic Lupus Erythematosus (SLE). Objectives: The aim of this study was to investigate the effects of belimumab given as an add-on to patients with active SLE despite standard-of-care therapy, with focus on low-active lupus nephritis (LN) patients. Methods: Fourteen patients were included. Clinical data were acquired at baseline and week 12, 26 and 52. Disease activity was assessed using SLE Disease Activity Index 2000 (SLEDAI-2K) and Systemic Lupus Activity Measure (SLAM). The primary organ manifestations comprised arthritis (n=9), skin involvement (n=11), serositis (n=3), involvement of the central nervous system (n=4) and cytopenias (n=3). Nine patients with former LN were included (median proteinuria at baseline 0.2 g/day, range 0.01-0.4 g/day). Results: At baseline, all patients received oral prednisolone (mean dose 11, range 5-20 mg/day), 9 received antimalarials, 3 mycophenolate mofetil, 2 azathioprine, and 1 cyclosporine. The median SLEDAI and SLAM scores were 10 (range 2-24) and 12 (range 5-23), respectively. One patient withdrew due to allergic reaction. Significant decreases of SLAM and SLEDAI were seen at week 26 (p=0.001 and p=0.007, respectively) and 52 (p=0.028 and p=0.012, respectively). Prednisolone dosages were significantly decreased compared to baseline at week 26 (p=0.003) and 52 (p=0.008). Ten patients had low complement at baseline. We observed no significant increase in C3/C4 levels. In the patients with former LN, no renal flare was observed during the observation period. The grade of proteinuria remained unchanged at week 26 (median 0.14 g/day, range 0.01-0.5 g/day) and 52 (median 0.13 g/day, range 0.02-0.24 g/day). No severe adverse events were noted. Conclusions: Belimumab treatment decreased SLE disease activity and reduced corticosteroid usage. Despite the limited number of patients, our observations indicate that belimumab may prevent renal flares and may be used in patients with former LN and persistent low-grade proteinuria. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3876